Predictors of anaemia among adolescent schoolchildren of Ghana. (2020) - Gosdin, Lucas; Tripp, Katie; Mahama, Abraham B.; Quarshie, Kate; Amoaful, Esi Foriwa; Selenje, Lilian; Sharma, Deepika; Jefferds, Maria Elena; Sharma, Andrea J.; Whitehead, Ralph D.; Suchdev, Parminder S.; Ramakrishnan, Usha; et al.
Abstract: Anaemia is a public health problem in Ghana. We sought to identify factors associated with haemoglobin concentration (Hb) and anaemia among school-attending adolescents. We analysed data from 2948 adolescent girls and 609 boys (10–19 years) selected from 115 schools from regions of Ghana as a secondary analysis of baseline surveys conducted at two time-points. We measured Hb, malaria from capillary blood, anthropometry and used a modified food frequency questionnaire to assess diet. Multivariable linear and Poisson regression models were used to identify predictors of Hb and anaemia. The prevalence of anaemia, malaria and geophagy were 24, 25, and 24 %, respectively, among girls and 13, 27 and 6 %, respectively, among boys. Girls engaging in geophagy had a 53 % higher adjusted prevalence of anaemia and 0⋅39 g/dl lower Hb. There were similar results among those who tested positive for malaria (+52 % anaemia; −0⋅42 g/dl Hb). Among girls, lower anaemia prevalence and higher Hb were associated with consumption of foods rich in haeme iron (−22 %; +0⋅18 g/dl), consumption of iron-fortified cereal/beverages consumed with citrus (−50 %; +0⋅37 g/dl) and being overweight (−22 %; +0⋅22 g/dl). Age was positively associated with anaemia among girls, but negatively associated among boys. Boys who tested positive for malaria had 0⋅31 g/dl lower Hb. Boys who were overweight or had obesity and consumed flour products were also more likely to be anaemic (119 and 56 %, respectively). Factors associated with Hb and anaemia may inform anaemia reduction interventions among school-going adolescents and suggest the need to tailor them uniquely for boys and girls.